Potential Spices Plants, Seasonings and Food Colorings in Dayak Tribe of Kubu Raya Regency - Suryani, Ade Irma; Afandi, Afandi; Pramulya, Muhammad (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
West Kalimantan has a tropical forest area that still holds a lot of potential plants as ingredients for spices, seasonings, and food coloring. Study This aim for register types plants that are used as spices, seasonings and colorings food by the community Dayak tribe of Regency Kubu Raya so that plant the can documented with good. Research This is study descriptive exploratory with approach qualitative method data collection carried out in a way triangulation with technique interviews, observations, and documentation. Selection respondents use technique purposive sampling, namely respondents chosen in a way on purpose based on criteria certain. Research results show there is as many as 57 types plants used by the community Dayak tribe of Regency Kubu Raya as spices, seasonings and colorings food. From 57 types these plants, 13 are classified as plant spices, 38 types plant spices, and 10 types plant colorings food.